Uncovering the differences of household carbon footprints and driving forces between China and Japan. (June 2022) - Yu, Feng; Dong, Huijuan; Geng, Yong; Fang, Alex S.; Li, Haifeng
Abstract: Household carbon footprint is closely related with economic development level. Thus, to reveal the characteristic of household carbon footprint and its driving forces for countries under different development stage, this paper compared household carbon footprint and driving forces of developing China and developed Japan using input-output method and structural decomposition analysis method. Results show that China's household carbon footprint increased rapidly from 939 megatons (Mt) in 1997–3363 Mt in 2015, and then gradually decreased, while Japan's household carbon footprint fluctuated between 700–1000 Mt. In terms of per capita indirect household carbon footprint, it increased fast in China, but was still only less than 1/4 of that in Japan in 2018. Another finding is that food carbon footprint will decrease, while housing carbon footprint will increase with economic development. Transportation & communication can be a potential source for reducing such carbon footprints. In terms of driving forces of household carbon footprint, consumption expenditure was the major positive driving force and technology was a major negative driving force in China, while Japan was mainly driven by technology. It is suggested to pay attention to control the per capita household carbon footprint of fast developing countries, particularly transportation & communication consumption. Highlights: Household carbon footprint (CF) of China and Japan during 1997–2018 is compared. Driving forces of household carbon footprint are analyzed using SDA method. Per capita indirect household carbon footprint of China is only 1/4 of Japan. Food CF decreases while housing CF increases with economic development. Household consumption expenditure and technology are main driving forces.